Bulk valley transport and Berry curvature spreading at the edge of flat bands - Subhajit Sinha (Nature Portfolio, 2020)
Spontaneous symmetry breaking of flat bands in twisted graphene systems may lead to anomalous Hall effect with a precursor state which has not been observed. Here, the authors probe this precursor state by observing bulk valley current and large nonlocal voltage several micrometers away from the charge current path in twisted double bilayer graphene.